The Formulation of Hypoallergenic Massage oil using Local Essential Oil of Indonesia - Chandrawati Cahyani; Herwinda Brahmanti; Luthfi Kurnia Dewi; Vivi Nurhadianty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2021)
A laboratory study was conducted to investigate the possibility of producing a hypoallergenic massage oil using local essential oil. The main concept behind the study was the application of massage oil formula which is in contact with skin need to be allergen free. This study used four types of local essential oil, i.e. cananga, clove, citronella and a fraction of citronella oil. Two types of carrier oils were used, i.e. extra virgin olive oil and grape seed oil. The study searches the concentration of essential oil which is safe to be used in the formula, not giving an allergy reaction. The concentration of essential oil studied were one and two percent respectively, and an allergy test will also be conducted to the carrier oil themselves. The allergy test was conducted toward 30 respondents.